Social Media Impact on Mental Health Using Data Analytics: A Classified Review - Jotawar, Rajendra; Gowda, Punu N (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
This study examines the complex relationship between social media use and mental health using a comprehensive methodology, highlighting both positive and negative effects. Social media has become a major source of dependency for many people who are struggling with mental health concerns. The phrase "social media" describes a broad category of digital platforms that allow users to engage with each other in a virtual community and exchange, co-create, or share various types of digital content, including messages, images, videos, and information. Examples of these platforms include Facebook, Instagram, Snapchat, LinkedIn, and Twitter. Studies have demonstrated that the rates of social media use by individuals with a variety of mental diseases, including psychotic disorders, depression, and other severe mental health issues, are comparable to those of the general population. Social media's pervasiveness has led to an explosion of studies examining its effects on mental health. This study applies data analytics to a thorough analysis of the body of literature, classifying the various conclusions using a hierarchical method. The study examines the possible advantages and disadvantages of social media use, investigating its connections to a range of mental health issues, such as social comparison, anxiety, and depression. The paper clarifies how data analytics may be used to comprehend the intricate link between social media and mental health by examining user behavior, linguistic trends, and content engagement. The study also highlights future prospects and constraints, emphasizing the necessity for longitudinal research and the ethical issues related to data collecting and processing in this field. With its insights into the complex effects of social media on mental health and its potential to stimulate more study and intervention techniques, this categorized review is an invaluable tool for academics, policymakers, and mental health practitioners.